2013
DOI: 10.1158/1078-0432.ccr-12-3725
|View full text |Cite
|
Sign up to set email alerts
|

S100B Promotes Glioma Growth through Chemoattraction of Myeloid-Derived Macrophages

Abstract: Purpose S100B is member of a multigenic family of Ca2+-binding proteins that is overexpressed by gliomas. Recently, we demonstrated that low concentrations of S100B attenuated microglia activation through the induction of Stat3. We hypothesized that overexpression of S100B in gliomas could promote tumor growth by modulating the activity of tumor-associated macrophages (TAMs). Experimental Design We stably transfected GL261 glioma cell lines with constructs that overexpressed (S100Bhigh) or underexpressed (S1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 62 publications
1
72
0
2
Order By: Relevance
“…In the current study, however, RAGE expression did not inhibit TAM infiltration in gliomas. This finding is consistent with our recent report demonstrating that S100B-mediated promotion of leukocyte trafficking into gliomas was not dependent on RAGE expression in TME, but mediated through upregulation of CCL2 (32). Similarly, Heijmans et al reported that lack of RAGE in colon polyps did not influence MP trafficking, but instead, caused a marked increase in infiltrating mast cells (33).…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, however, RAGE expression did not inhibit TAM infiltration in gliomas. This finding is consistent with our recent report demonstrating that S100B-mediated promotion of leukocyte trafficking into gliomas was not dependent on RAGE expression in TME, but mediated through upregulation of CCL2 (32). Similarly, Heijmans et al reported that lack of RAGE in colon polyps did not influence MP trafficking, but instead, caused a marked increase in infiltrating mast cells (33).…”
Section: Discussionsupporting
confidence: 94%
“…45,69 ) Chronic lymphatic leukemia Drug resistance in leukemia cells asociated with upregulation of glyoxalase I, HMGB1 levels increased in pts with CLL and HMGB1 concentration associated with absolute lymphocyte cell count, CLL cells passively release HMGB1, release of HMGB1 related to the differentiation of nurse-like cells (NLC), S100A8 promotes (through RAGE activation) autophagy of leukemia cells and contributes to the drug resistance of leukemia cells (ref. 35,47 ) Lymphoma S100A2 expression observed in lymphoma biopsies (ref.…”
Section: Type Of Cancer Rage Ligandmentioning
confidence: 99%
“…S100B is overexpressed by gliomas and its downregulation of S100B abrogates tumor growth in vivo and is related to higher infiltration with tumor-associated macrophages, stronger inflammatory response and increased vascularity. As RAGE ablation had no effect on the infiltration of gliomas with tumor-associated macrophages, other pathways (possibly CCL2 expression) may be involved and could be targeted 69 . S100B expression may also be a prognostic marker in malignant melanoma 70 .…”
Section: S100 Proteins and Cancermentioning
confidence: 99%
“…Phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced pro-inflammatory mediators were shown to be decreased in RAGE-deficient mice (7) which suggests that RAGE expression is involved in sustaining inflammation and skin and pancreatic cancer (1-2,7,9). It has also been well documented that RAGE ligands bind to RAGE and activate its downstream signaling mechanisms that fuel chronic inflammatory conditions leading to neoplastic stage (1,12-13). It is interesting to note that there is very low or no RAGE expression in normal tissues, but enhanced expression in chronic inflammation and cancer (2,10).…”
Section: Introductionmentioning
confidence: 99%